Identifying Central Carriers and Detecting Key Communities Within the Global Fish Transshipment Networks - Petrossian, Gohar A.; Barthuly, Bryce; Sosnowski, Monique C. (Frontiers in Marine Science, 2022)
To effectively monitor fisheries resources and combat illegal, unreported, and unregulated fishing, human labor exploitation onboard fishing vessels amongst other crimes, such as the trafficking of weapons, humans, and narcotics, it is important that more attention is paid to the likely facilitators of these activities, one of these being at-sea transshipment of fish. Even though transshipment is a common practice that has taken place for decades, little is known about the overall networks, operational practices, and global spatial patterns of the central actors involved in such activities. This research aims to fill that knowledge gap by understanding the networks of activities of the actors who play a central role in these global transshipment activities. Using data from Global Fishing Watch on global transshipment events that took place between 2015 and 2020, this research (a) identifies the central carriers involved in transshipment events, (b) visualizes their networks of activities and interactions with fishing vessels, (c) examines the spatial distribution of their activities; and (d) determines whether these vessels use open-registry flags when engaging in transshipments, and if so, which. In exploring the role that central actors play within networks of transshipments, targeted mechanisms can be designed to better monitor such activities.